PROBLEME DAYALI ÖĞRENME YAKLAŞIMININ ÖĞRENCİLERİN FEN DERSLERİNDEKİ AKADEMİK BAŞARILARINA ETKİSİ: BİR META-ANALİZ ÇALIŞMASI. - AYAZ, Mehmet Fatih (Electronic Turkish Studies)
Introduction and Purpose In that days expectations from individuals are relation to information, evaluate the information, use the information effectively; requirement of information literateness (Erdem and Akkoyunlu, 2002: 3). Teachers working with constructivist learning strategies in courses is determined to save the development of students' scientific knowledge, life skills and academic achievement (ılter, 2013: 594). The most important one of the strategies is the problem-based learning (PBL) approach. The curriculum in Turkey are reformed in 2005 with constructivist learning approach by taken to the centre. In addition to this PBL approach's importance is increased and this approach's importance exposed in many researches with education process. In Turkey, there are many studies about the subject of "Problem-Based Learning Approach" (Tavukcu, 2006; Özyalçın Oskay, 2007; Bayrak, 2007; Tatar, 2007; Akın, 2008; ınel, 2009; Kartal Taşoğlu, 2009; Tosun, 2010; Şahbaz, 2010; Moralar, 2012). Especially in spite of to clear the effect of PBL approach's academic achievement in science lessons which is about science area. Researches which done from different perspectives about PBL approach subject needs to combine, synthesis and evaluate. In this respect there is an importance to find answer to "How has an effect of problem-based learning approach to students' academic achievement in science lessons?"question with meta-analysis method. Under general purpose, to determine differences between effect sizes of studies' characteristics that included to meta-analysis. Method Meta-analysis is statistical method to unit the similar studies' results. Meta-analysis supply comparing of many researches results by changing to common measure unit and also supply to account the effect size by statistical process (Cohen, Manion and Morrison, 2007; Cooper, 2010; Ergene, 1999; Hedges and Olkin, 1985; Hunter and Schmidt, 1990; Rudy, 2013). The scales can not be same in studies and can have inconsistent values which included into research. For that difference between groups which PBL approach used or did not use by standard for suitable in meta-analysis statistics studies with sample method, used standardized arithmetic average differences effect size (Cohen, 1988; Huffcutt, 2002; Hunter and Schmidt, 1990; Lipsey and Wilson, 2001; Rosenthal, 1991; Schulze, 2004; Wolf, 1986). We use classifications when comment importance of metaanalysis results' effect size. Effect size classification by Cohen and others are as follows (2007: 521): • 0 ⩽ Effect size value ⩽ 0,20 "poor", • 0,21 ⩽ Effect size value ⩽ 0,50 "modest", • 0,51 ⩽ Effect size value ⩽ 1,00 "moderate", • 1,01 ⩽ Effect size value has "strong" effect level. The studies which included to research, formed from master and doctoral dissertations between 2003-2013 in Turkey about "Problembased Learning" subject and own research problems and needed statistical datas. Search of postgraduate dissertations in Turkey done between the dates of 23.09.2014 and 22.12.2014 as Turkish and English from Council of Higher Education National Dissertations Centre web site. With the results of examinations the total number of will be combined of the studies in the meta-analysis has been identified as 24. Study codifications done by two researchers. They have graduated master degree in Educational Sciences. The reliability found %96 by using reliability level formula (Miles and Huberman, 2002). Obtained %70 and more than it values are reliable enough for it (Yıldırım and Şimşek, 2011: 233). Findings and Discussion In this study transaction effect meta-analysis is used in analyzing of datas. According to random effect model, general effect size of studies is 1,206 (%95 CI, SE=0,177) with 0,859 and 1,554 confidence interval. It is strong level for Cohen, Manion and Morrison (2007) effect size classification. When we examine effect sizes of studies, it determined minimum effect size value is 0,142, maximum effect size is 3,344. When we look effect size of studies, all of 24 studies are pozitive. With Orwins' method to drop this effect size level (1,206) to zero (0,01), needed number of studies found 2404 which's effect size values are zero. That shows publication bias has a low level. Results and Recommendations Totally 24 studies stated about effect of PBL approach to students' academic achievement in science lessons. When we calculate homogenity value of studies based on fixed effect model, we found it Q=225,776. In χ table meaning level of %95 for twenty-three degree of freedom value found as 35,172. Statistical value of Q=225,776 passed over twenty-three degree of freedom value (for df=23, χ (0,95)=35,172). So we used random effect model to calculate effect size of studies. When we calculate homogenity value of studies based on random effect model, we found it Q=26,109. Statistical value of Q=26,109 did not pass over twenty-three degree of freedom value (for df=23, χ (0,95)=26,109). It is determined that PBL approach have a positive effect to students 'academic achievement in science lessons in order to determine its effect on the results of the meta-analysis of the PBL approach based on traditional learning methods to students' academic achievement in science lessons. According to the results of research; PBL approach have the highest effect size values at PhD dissertations, in chemistry, at primary school, in written materials, at more than 30 students and more than 20 hours. According to the results of research; PBL approach have the lowest effect size values at master thesis, in biology, at secondary school, at between 1 and 29 students and between 1 and 20 hours. With the results and the experiment in study process in research, these recommendations to be given to practitioners, program developers and researchers: - To determine PBL approach's effect to students' academic achievement in science lessons motivated meta-analysis study result; PBL approach has strong level pozitive effect in students' academic achievement in science lessons than traditional education methods. Science teachers can use PBL approach for effective learning. - It identified that PBL approach has higher effect on students' academic achievement in chemistry. Therefore PBL approach specially can use in chemistry field. - When we look PBL approach effect size on students education level, the highest effect size is at primary school level. But all of education levels have strong effect size level. So PBL can be used at all education levels. - For sample size classification; PBL approach can be used more than 30 students in a class which effect size value is more higher. - For practice time of studies; PBL approach can be used in more than 20 hours. Due to subjects time shouldn't be kept short and should allow time to students to change pozitive attitude. - Studies with different effect size levels can be examined one by one and it can be determined these differences effect from what sort of factors. - There can be more studies about PBL approach in primary and high schools, then their effect size can be analyzed again so it will be benefit for giving correct results. - Studies about PBL approach included to meta-analysis generally made as level of secondary school and university. There can be made researches with 4+4+4 education system type.